2006
DOI: 10.1002/jhm.94
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes care in the hospital: Is there clinical inertia?

Abstract: BACKGROUND Effective control of hospital glucose improves outcomes, but little is known about hospital management of diabetes. OBJECTIVE Assess hospital‐based diabetes care delivery. DESIGN Retrospective chart review. SETTING Academic teaching hospital. PATIENTS Inpatients with a discharge diagnosis of diabetes or hyperglycemia were selected from electronic records. A random sample (5%, n = 90) was selected for chart review. MEASUREMENTS We determined the percentage of patients with diabetes or hyperglycemia d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 39 publications
6
73
1
2
Order By: Relevance
“…[14][15][16] Clinical inertia is defined as the failure to intensify therapy when needed. 17 We first described clinical inertia in the hospital with regards to insulin administration in 2006, 18 with further evidence found subsequently. 19 Others have also observed clinical inertia in the treatment of inpatient diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Clinical inertia is defined as the failure to intensify therapy when needed. 17 We first described clinical inertia in the hospital with regards to insulin administration in 2006, 18 with further evidence found subsequently. 19 Others have also observed clinical inertia in the treatment of inpatient diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In general medicine and surgery services, however, hyperglycemia is frequently overlooked and inadequately addressed. Several reports from academic institutions have shown that most patients are treated with SSI and that basal insulin is prescribed in less than one-half of patients (16,17). Few clinical trials have focused on the optimal management of inpatient hyperglycemia in the noncritical setting.…”
mentioning
confidence: 99%
“…Estudios similares publicados muestran cifras comparables a nuestra realidad; Schnniper et al, en un estudio prospectivo de 107 pacientes diabéticos en una unidad de medicina no crítica, publicado el año 2006, reporta 76% de pacientes con glicemias sobre 180 mg/dl y 11% de pacientes con un episodio de glicemia inferior a 60 mg/dl 20 ; un estudio de 44 hospitales de Estados Unidos de Norteamérica muestra 77% de pacientes con glicemias superiores a 200 mg/dl, y 12% de episodios de hipoglicemia bajo 60 mg/dl 21 . Sin duda, el control glicémico previo a la hospitalización tiene que ver con la evolución del paciente; sin embargo, también se han invocado factores como la inercia clínica, es decir, la falta de toma de decisiones respecto de la hiper o hipoglicemia, a la tolerancia ante cifras elevadas como grandes responsables de esta situación 5,22 Control glicémico en diabéticos hospitalizados en camas no críticas -I. Solís et al estos hechos. Nuestro trabajo no profundiza en la toma de decisiones ni en diversos esquemas de tratamiento con insulina, aunque el uso de escalas (sliding scales) de insulina cristalina cada 6 horas es una práctica habitual y muy arraigada en nuestra cultura médica y tiene que ver con grandes fluctuaciones glicémicas y un demostrado mayor riesgo de descontrol metabólico 8 .…”
Section: Discussionunclassified
“…XXIX Congreso Chileno de Medicina Interna, Santiago de Chile, 2007). Esta proporción es coincidente con la descrita por otros autores 4,5 y en el sistema público nacional 6 . En los pacientes diabéticos se invierte el doble de los recursos que en los no diabéticos en cuanto a farmacia, insumos y recursos de personal involucrados 7 .…”
unclassified